2017
DOI: 10.1161/atvbaha.116.308932
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sortilin Associates With Aortic Calcification and Cardiovascular Risk in Men

Abstract: Objective GWAS and preclinical studies demonstrated a role of sortilin in lipid metabolism, inflammation, and vascular calcification – all cardiovascular risk factors. We evaluated the association of serum sortilin levels with the risk of major adverse cerebrovascular and cardiovascular events (MACCE) and the severity of abdominal aortic calcification (AAC). Approach and Results A cohort of community-dwelling men aged ≥50 (n=830) was assessed. At baseline, sortilin levels were measured by ELISA, and AAC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…Our findings of dimerized soluble sortilin have important implications in a clinical setting because serum sortilin can act as a biomarker for cardiovascular and neurologic diseases ( 31 33 ). Therefore, it is important to clarify the differences between monomers and dimers of soluble sortilin and the monomer/dimer ratio in serum for these diseases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings of dimerized soluble sortilin have important implications in a clinical setting because serum sortilin can act as a biomarker for cardiovascular and neurologic diseases ( 31 33 ). Therefore, it is important to clarify the differences between monomers and dimers of soluble sortilin and the monomer/dimer ratio in serum for these diseases.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies reported that serum sortilin levels are associated with cardiovascular risk, such as aortic calcification ( 31 ) and atherothrombosis ( 32 ), as well as depression ( 33 ). Soluble sortilin can also activate survival pathways in cancer cells ( 6 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sortilin has been previously associated with cardiovascular disease, and metabolic and adipose tissue functions 13 16 , 18 23 , 37 ; however, the connection of Sortilin between atherosclerosis and obesity, including its mechanistic role has not been established. The nuclear receptor, LXR reduces atherosclerotic lesion when activated in several models, but can also induce hepatic steatosis 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Sortilin has been associated with atherosclerosis, very-low density lipoprotein secretion, macrophage LDL uptake and foam cell formation, inflammatory cytokine secretion, and hepatic steatosis 17 21 . Additionally, we recently established a mechanistic role of Sortilin in the loading of extracellular vesicles contributing to cardiovascular calcification 22 , along with associating elevated serum Sortilin to aortic calcification and cardiovascular risk 23 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, it is feasible to speculate that the serum sortilin level may interact with inflammatory response and be related to CHD susceptibility. Additionally, clinical studies identified sortilin as a risk factor for cardiovascular disease, 16 and SORL1 is also considered to contribute to the development of atherogenesis. 17 However, the mechanism is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%